L.G. Damas, seul et soul dancer de la négritude - Gyssels, Kathleen (Ponti/Ponts, 2021)
In Leon Damas’ poetry, the musical traditions from the Plantation universe merge with the modernist jazz which developed rapidly in the big metropolises (Harlem, Paris, Marseille,…). In this article, I illustrate how Damas uses the musical mode to express through dance the forbidding crossing of Lines (the Color Line, class and gender). His poetry is transgressive in that he shows the “transe” obtained in the magical rhythms and genres, which allow the poet to liberate himself from the boundaries of race, class, and genre.